2013
DOI: 10.1002/met.1355
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation of analysis methods for sub-annual extreme wind speeds

Abstract: This paper consolidates recent advances in methodologies in extreme-value analysis of wind speeds by using sub-annual maxima in conjunction with exact and penultimate extreme-value models. By avoiding asymptotic models and the associated issues of asymptotic convergence, the consolidated methodology is able to extend analysis further into the lower tail, greatly increasing the statistical confidence. The standard error in design predictions of dynamic pressure is reduced to less than a third of the correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Statistical modeling of wind extremes remains an active research area (Harris 2005(Harris , 2009Makkonen 2008;Cook 2012Cook , 2014Makkonen et al 2013;Torrielli et al 2013). However, a number of analyses have shown that the annual maxima of wind speeds fit reasonably well to Gumbel distribution especially when wind speeds conform to the three-parameter Weibull distribution (Van den Brink and Können 2008; Pryor et al 2012a).…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Statistical modeling of wind extremes remains an active research area (Harris 2005(Harris , 2009Makkonen 2008;Cook 2012Cook , 2014Makkonen et al 2013;Torrielli et al 2013). However, a number of analyses have shown that the annual maxima of wind speeds fit reasonably well to Gumbel distribution especially when wind speeds conform to the three-parameter Weibull distribution (Van den Brink and Können 2008; Pryor et al 2012a).…”
Section: Methodsmentioning
confidence: 98%
“…Estimates of extreme wind speeds at different return periods are usually computed using the Extreme Value Theory (Coles 2001). Several approaches have been suggested to compute quantiles at different return periods such as fitting annual maxima to Generalized Extreme Value (GEV) (Anastasiades and McSharry 2013) or Gumbel distribution, fitting the data over a threshold to Generalized Pareto Distribution (POT/GPD) (Holmes and Moriarty 1999), fitting r-largest values to GEV (Coles 2001), and extracting data using the Method of Independent Storm (IMIS or XIMIS) (Cook 1982;Harris 1999Harris , 2009) and building a Poisson process model (Cook 2014).…”
Section: Methodsmentioning
confidence: 99%
“…The XIMIS method [11], fitted by weighted least-mean-squares (wLMS) and displayed on Gumbel axes, was preferred [12] over other extreme-value analysis (EVA) methods for the following reasons:…”
Section: The Ximis Methods Of Extreme-value Analysismentioning
confidence: 99%
“…The accuracy of ( 5) and ( 6) is assessed in [12]. The distributions of plotting position around the mean, y m , are also the distributions of the m-th highest values for repeated samples of the observation period, R. In practice, as there is only one observation period, the distributions of the m-th highest values are used to assess the confidence that can be placed in the individual values of that one sample.…”
Section: Ximis Methodologymentioning
confidence: 99%
See 1 more Smart Citation